Respiratory Effects of Exposure to Traffic-Related Air Pollutants During Exercise - Morici, Giuseppe; Cibella, Fabio; Cogo, Annalisa; Palange, Paolo; Bonsignore, Maria R. (Frontiers in Public Health, 2020)
Traffic-related air pollution (TRAP) is increasing worldwide. Habitual physical activity is known to prevent cardiorespiratory diseases and mortality, but whether exposure to TRAP during exercise affects respiratory health is still uncertain. Exercise causes inflammatory changes in the airways, and its interaction with the effects of TRAP or ozone might be detrimental, not only for athletes exercising outdoor, but also for urban active commuters and the middle-aged population. In this Mini-Review, we summarize the literature on the effects of exposure to TRAP and/or ozone during exercise on lung function, respiratory symptoms, performance, and biomarkers. Ozone negatively affected pulmonary function tests after exercise, especially in case of combined exposure to ozone and diesel exhaust (DE). Changes in spirometry after exercise during exposure to other pollutants, i.e. particulate matter and ultrafine particles, suggest a decrease in lung function, especially in patients with chronic obstructive pulmonary disease. Ozone frequently caused respiratory symptoms during exercise. Women showed decreased exercise performance, and high prevalence of symptoms, during TRAP exposure compared to men. However, exercise performance was analyzed in few studies. To date, research on TRAP-related lung damage has not identified reliable biomarkers to be used to monitor athletes’ health, except in the few studies on airway cells obtained by induced sputum or bronchoalveolar lavage. In conclusion, TRAP exposure likely exerts detrimental effects on respiratory health, at least partly counteracted by the positive effects of habitual exercise. Further studies are needed to identify safety threshold for outdoor exercise in cities.